The Impact of the Revised WIC Food Package on Maternal Nutrition During Pregnancy and Postpartum. Issue 8 (16th May 2019) - Hamad, Rita; Batra, Akansha; Karasek, Deborah; LeWinn, Kaja Z; Bush, Nicole R; Davis, Robert L; Tylavsky, Frances A
Abstract: The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) provides nutritional support for pregnant and postpartum women and young children. The typical food package provided to recipient families was revised in October 2009 to include more whole grains, fruits, vegetables, and low-fat milk. Little is known about whether these revisions improved nutrition among women during this critical period of the life course. We conducted a quasiexperimental difference-in-differences analysis, comparing WIC recipients ("treatment" group) before and after the WIC policy change, while accounting for temporal trends among nonrecipients ("control" group). We examined nutritional outcomes among a cohort of 1, 454 women recruited during pregnancy in 2006–2011 in Memphis and surrounding Shelby County, Tennessee. We found improvements in several measures of dietary quality and nutrient intake during pregnancy, although these did not persist into the postpartum period. Results were robust to numerous sensitivity analyses. At a time when federal WIC funding is threatened, this study provides some of the first evidence of the benefits of recent WIC revisions among low-income women.